Implementasi Undang-Undang No. 6 Tahun 2014 (Studi Kasus Program Gerbang Sadu Mandara di Desa Manukaya) - Suardika, I Putu Adi; Winaya, I Ketut; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2018)
ABSTRACT The birth of Constitution No. 6 of 2014 leads to villages having their own autonomy. This then makes every program run in the village self-administered by participatory village governance including the implementation of the Gerbang Sadu Mandara program. Result of the analysis shows that the Gerbang Sadu Mandara program has been running well. Communication programs already supported by transmission, clarity, and consistency of policy makers. Variables of resources there are staff, the authority, information, and facilities have been formulated and provided by the Government of the village. Disposition of the commissioning program has been formulated in the deliberation of the village whom the appointment of bureaucrats who have the ability and willingness, and supported with incentives given to executing programs. Bureaucratic structure in the form of Standard Operating Procedures (SOPs) of the policy makers supported by SOPs created and implemented by implementing policies. Keyword: Constitution No. 6 of 2014, Gerbang Sadu Mandara